Selenium in animal feeds and nutrition - Root, Tarja (MTT, 2005)
Selenium (Se) is an essential nutritional trace element, which is needed for growth and reproduction in all living animals. At the same time it is a highly toxic substance, and therefore the Se content of animal diets should be monitored constantly. The dietary requirement of Se differs between the animal species and is affected by the form of selenium ingested and dietary composition, especially its content of vitamin E. The Finnish recommendation of Se for cattle is 0.1 mg/kg feed DM, for pigs 0.2 mg/kg DM, for poultry 0.1-0.2 mg/kg DM and fur animals 0.6- 0.9 mg/kg DM. The level of Se in feeds of plant origin varies depending on plant species, part of the plat, growing season and soil which the plants grow on. In Finnish soils the selenium availability to plants is limited, and Se addition to fertilizers has increased the overall Se content of feed materials from 0.02 mg/kg dry matter (DM) to 0.2 mg/kg DM. The best Se sources of the feeds of animal origin are fish products. The main form of selenium in plant and animal origin feed materials is organic protein-bound selenomethionine, together with small amounts of selenocysteine and selenite. Animal feeds and diets can also be supplemented with inorganic selenium (sodium selenite, sodium selenate). However, at present the organic selenium sources are not accepted as feed additives. The maximum permitted amount of Se in compound feeds or daily rations is 0.5 mg/kg DM.
Keywords: Ka; selenium; animal nutrition; feed